2010
DOI: 10.2332/allergolint.10-rai-0260
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Immune Reconstitution Syndrome Necessary for Better Management of Patients with Severe Drug Eruptions and Those under Immunosuppressive Therapy

Abstract: The immune reconstitution syndrome (IRS) is an increasingly recognized disease concept and is observed with a broad-spectrum of immunosuppressive therapy-related opportunistic infectious diseases and severe drug eruptions complicated by viral reactivations. Clinical illness consistent with IRS includes tuberculosis, herpes zoster, herpes simples, cytomegalovirus infections and sarcoidosis: thus, the manifestations of this syndrome and diverse and depend on the tissue burden of the preexisting infectious agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 58 publications
0
49
1
Order By: Relevance
“…In addition, Shiohara et al (9) reported that DIHS is a manifestation of immune reconstitution syndrome (IRS). IRS was originally defined as a paradoxical deterioration in clinical status attributable to the recovery of immune response in HIV patients receiving highly active antiretroviral therapy (HAART) (10).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, Shiohara et al (9) reported that DIHS is a manifestation of immune reconstitution syndrome (IRS). IRS was originally defined as a paradoxical deterioration in clinical status attributable to the recovery of immune response in HIV patients receiving highly active antiretroviral therapy (HAART) (10).…”
Section: Discussionmentioning
confidence: 98%
“…IRS was originally defined as a paradoxical deterioration in clinical status attributable to the recovery of immune response in HIV patients receiving highly active antiretroviral therapy (HAART) (10). Based on the concept of IRS, various opportunistic infectious diseases occur or recur on a reducing dose or withdrawal of immunosuppressive agents such as PSL (9).…”
Section: Discussionmentioning
confidence: 99%
“…This would reduce the viral load, but may also cause tissue damage (4). As such, DIHS is considered to be another manifestation of immune reconstitution syndrome (IRS) (11). In order to suppress immune reactions, systemic corticosteroid administration is typically recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Foxp3 + Tregs were shown to expand quickly during the course of immune reconstitution; thus, these expanded Tregs could act to prevent lymphopenia-associated autoimmunity in individuals recovering from lymphopenia in mice (29). Importantly, similar expansions of fully functional Tregs during the acute phase and the subsequent contraction upon resolution of disease as observed in EH also were reported to occur in patients with sarcoidosis or drug-induced hypersensitivity syndrome (30,31), both of which fit within the spectrum of immune reconstitution syndrome (32,33). In a recent retrospective analysis (1) of 100 cases of EH, 36% of the patients had noted a severe exacerbation of their AD that typically had started ∼2 wk before the onset of EH, and the majority of the patients had not received any corticosteroid therapy in the 4 wk before the onset of EH.…”
Section: Hsv-specific Cd4mentioning
confidence: 75%